Effects of spent substrate of oyster mushroom (Pleurotus ostreatus) on ruminal fermentation, microbial community and growth performance in Hu sheep - Lu, Mu-Long; Yuan, Guo-Hong; Rehemujiang, Halidai; Li, Chang-Chang; Hu, Li-Hong; Duan, Ping-Ping; Zhang, Li-Dong; Diao, Qi-Yu; Deng, Kai-Dong; Xu, Gui-Shan (Frontiers in Microbiology, 2024)
The study aimed to evaluate the effects of Pleurotus Spent Mushroom Substrate (P.SMS) on the rumen microbiota, encompassing bacteria and fungi, as well as their interactions in Hu sheep. A total of forty-five 3-month-old Hu sheep were randomly assigned to five groups. Each group was fed diets in which whole-plant corn silage (WPCS) was substituted with P.SMS at varying levels: 0% (CON), 5% (PSMS5), 10% (PSMS10), 15% (PSMS15), or 20% (PSMS20). The results indicated that higher proportions of P.SMS during the experimental period might have a detrimental effect on feed utilization efficiency, kidney function, and blood oxygen-carrying capacity. Notably, moderate levels of P.SMS, specifically below 15%, were associated with improvements in rumen NH3-N levels and absorption capacity. The results indicated that (1) PSMS20 exhibited a significantly higher feed-to-gain ratio compared to CON (P < 0.05); (2) PSMS15 showed a significantly higher NH3-N content than CON, PSMS5, and PSMS20. Additionally, PSMS10 and PSMS20 had elevated concentrations of NH3-N compared to CON and PSMS5 (P < 0.05); (3) The length and width of rumen papillae were significantly greater in PSMS20 compared to CON and PSMS5 (P < 0.05); (4) Creatinine levels were significantly higher in PSMS20 than in CON, PSMS5, and PSMS10 (P < 0.05); (5) By the conclusion of the experiment, hemoglobin concentration in PSMS20 showed a significant increase compared to CON (P < 0.05). Furthermore, the addition of P.SMS influenced microorganisms at both the phylum and genus levels: (1) At the phylum level, the prevalence of Patescibacteria was significantly lower in PSMS20 compared to the other groups; (2) PSMS15 exhibited significantly higher relative abundances of Basidiomycota compared to CON and PSMS10, while PSMS20 also demonstrated significantly higher relative abundances compared to CON (P < 0.05); (3) At the genus level, the prevalence of Candidatus_Saccharimonas in PSMS20 was significantly lower than in PSMS5, PSMS10, and PSMS15. Conversely, the prevalence of Phanerochaete in PSMS15 was notably higher than in CON and PSMS10, and it was also significantly elevated in PSMS20 compared to CON (P < 0.05); (4) Correlation analysis indicated no significant correlation between changes in the structure of bacterial and